2011
DOI: 10.1007/s00167-011-1766-8
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty in severe haemophilic patients under continuous infusion of clotting factors

Abstract: Therapeutic study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…The intraarticular haematoma might easily occur after any arthroplasty, especially in TKA. Studies have reported the incidence of postsurgical bleeding to be 3-52% with a higher risk in the first week [4,6,7]. In our group, the rate of intraarticular haematoma was less than what was previously reported.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…The intraarticular haematoma might easily occur after any arthroplasty, especially in TKA. Studies have reported the incidence of postsurgical bleeding to be 3-52% with a higher risk in the first week [4,6,7]. In our group, the rate of intraarticular haematoma was less than what was previously reported.…”
contrasting
confidence: 69%
“…In an evaluation of data from all over the world of survival rates in multifoetal reduction, a lower survival rate has been reported in case of higher order multiple pregnancies as compared to lower order pregnancies i.e. up to quadruplets [7].…”
mentioning
confidence: 99%
“…Wong et al recommended coagulation factor replacement at a higher level for a longer period than in the current World Hemophilia Foundation guidelines. It is possible that the prevalence of bleeding may have been decreased if we had used a high coagulation factor replacement regime, maintaining a 100% level of coagulation factor throughout the first 3 weeks following TKA …”
Section: Discussionmentioning
confidence: 99%
“…The Japanese guideline for hemophilia treatment suggest to use CI for major surgery [35,36]. Many reports demonstrated CI to be safe and hemostatically effective for all indications mentioned above, including the most demanding surgical procedures [1,2,[4][5][6][7]20,[34][35][36][37][38]. Most recently Takedani [37], Rahmé et al [38], and Chevalier et al [39] reported on successful use of CI in 28, 20, and 72 total knee replacements, respectively.…”
Section: Prevention Of Thrombophlebitismentioning
confidence: 99%
“…Many reports demonstrated CI to be safe and hemostatically effective for all indications mentioned above, including the most demanding surgical procedures [1,2,[4][5][6][7]20,[34][35][36][37][38]. Most recently Takedani [37], Rahmé et al [38], and Chevalier et al [39] reported on successful use of CI in 28, 20, and 72 total knee replacements, respectively. A prospective controlled study comparing CI and BI for major surgery using protocols that were similar regarding the surgical technique and postoperative target minimum levels demonstrated that efficacy and safety were better with CI than with BI in terms of minimum factor levels achieved, blood loss (as measured by a decrease in hemoglobin level), blood transfusion requirements, and bleeding complications ( [24].…”
Section: Prevention Of Thrombophlebitismentioning
confidence: 99%